Molecular detection of foodborne pathogens - Liu, Dongyou (CRC Press, 2010)
While the vast majority of our food supplies are nutritious and safe, foodborne pathogen-related illness affects millions of people each year. This title discusses detection techniques. It demonstrates how to implement a surveillance system that uses molecular techniques to quickly detect and identify bacterial, viral and parasitic pathogens.